(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
The purpose of Law No. 26.485 ,enacted in 2009, is to provide Integral Protection to Prevent, Punish and Eradicate Violence against Women in the Environments in which they Develop their Interpersonal Relations. This law defines violence against women, creates the National Council of Women, which, among other competencies, must design and implement registers of situations of violence against women, establishing basic indicators on the phenomenon. The Single Registry of Cases of Violence against Women (RUCVM), created in 2012 from an agreement between the Women Council and the INDEC (National Statistics and Census Institute), was launched with the aim of collecting and systematizing the existing information in the records of cases of violence. In this article we offer a synthesis of the most relevant issues and problems related to the implementation of a Single Registry of Cases of Violence against Women. While it is true that the RUCVM data are only the top of the iceberg, they provide comparable statistics and also allow the design of public policy of violence against women in three levels: national, provincial and local.